Trib1 Is Overexpressed in Systemic Lupus Erythematosus, While It Regulates Immunoglobulin Production in Murine B Cells - Simoni, Léa; Delgado, Virginia; Ruer-Laventie, Julie; Bouis, Delphine; Soley, Anne; Heyer, Vincent; Robert, Isabelle; Gies, Vincent; Martin, Thierry; Korganow, Anne-Sophie; San Martin, Bernardo Reina; Soulas-Sprauel, Pauline (Frontiers in Immunology, 2018)
Systemic lupus erythematosus (SLE) is a severe and heterogeneous autoimmune disease with a complex genetic etiology, characterized by the production of various pathogenic autoantibodies, which participate in end-organ damages. The majority of human SLE occurs in adults as a polygenic disease, and clinical flares interspersed with silent phases of various lengths characterize the usual evolution of the disease in time. To date, we have no molecular explanation to the phenotype of SLE patients during silent phases and no explanation of the establishment and the maintenance of these clinically silent phases. Trying to understand the mechanism of the different phenotypic traits of the disease notably during remission phases, and considering the central role of B cells in SLE, we previously performed a detailed wide analysis of gene expression variation in B cells from quiescent SLE patients. This analysis pointed out an overexpression of TRIB1. TRIB1 is a pseudokinase that has been implicated in the development of leukemia and also metabolic disorders. It is hypothesized that Trib1 plays an adapter or scaffold function in signaling pathways, notably in MAPKs pathways. Therefore we planned to understand the functional significance of TRIB1 overexpression in B cells in SLE. We produced a new knock-in model with B-cell specific overexpression of Trib1. We showed that overexpression of Trib1 specifically in B cells doesn’t impact B cell development nor induce any development of SLE symptoms in the mice. By contrast, Trib1 has a negative regulatory function on the production of immunoglobulins, notably IgG1, but also on the production of autoantibodies in an induced model. We observed a decrease of Erk activation in BCR-stimulated Trib1 overexpressing B cells. Finally, we searched for Trib1 partners in B cells by proteomic analysis in order to explore the regulatory function of Trib1 in B cells. Interestingly, we find an interaction between Trib1 and CD72, a negative regulator of B cells whose deficiency in mice leads to the development of autoimmunity. In conclusion, the overexpression of Trib1 in B cells could constitute one of the molecular pathways implicated in the establishment and maintenance of clinically silent phases during SLE.